APAKAH KUALITAS WEBSITE BERDAMPAK PADA MINAT BELI DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING? - Vivi Iswanti Nursyirwan; Sasmita Sari Ardaninggar; Nina Valentika (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
Marketing is the process by which companies create value for customers and build strong relationships to capture value from customers in return. The main objective of this study is to determine the effect of website quality on purchase intentions and also customer trust as an intervention. The research object is the population of Shopee users who have been categorized as sample criteria. The criteria are S1 Accounting students at Universitas Pamulang and have online shopping experience through Shopee. Based on SEM-PLS data, this research is valid and reliable, the research model is also considered strong. This study proves the study of pre-existing theories and strengthens the results of hypothesis testing with the results of all variables having a positive and significant effect on purchase intention. The model in this study can be used as managerial implications for e-commerce based business development